Hz. Peygamber'in nübüvvet delili olarak ahlâk - Aktaş, Eda (My University, 2019)
İnsan hayatının her saha ve aşamasında din belirleyici bir rol oynamaktadır. Din, yaratıcı ile insanlar arasındaki ilişkiyi tesis etmekte, dünya ve ahiret mutluluğuna ulaştıracak öğretiler ihtiva etmektedir. İslâm dininin üç ana esası uluhiyet, nübüvvet ve ahirettir. Aşkın bir varlık olan yaratıcı ile fizik âlemdeki insan arasındaki ilişki vahiy ve nübüvvet aracılığıyla sağlanabilmektedir. Bu nedenle İslâm düşüncesinde nübüvvet müessesibüyük bir önem taşır. Nübüvvete yöneltilen itirazlar kelâm, felsefe ve tasavvuf ekollerince fikrî zeminde tartışılmıştır. İslâm dini evrensel olduğu için bu dinin peygamberi olan Hz. Muhammed’in risâleti de bütün insanlığı muhatap almaktadır. Bu nedenle her dönemde Hz. Muhammed’in nübüvveti aklî ve naklî delillerle ele alınmıştır. Nübüvvetin başka açılardan ele alınması zihnî olgunlukları ve kavrayış kabiliyetleri birbirinden farklı olan insanların bu müesseseye dair şüphelerini giderme veya imanlarını sağlamlaştırma imkânı tanıyacaktır. Bu fikirde olan İslâm mütefekkirleri Hz. Muhammed’in nübüvvetini ele alırken mucizeye dayandırmakla kalmamış, O’nun ahlâkını da ön plana çıkararak böylesine yetkin bir ahlâkın ancak bir peygamberde bulunabileceğini ispatlamaya çalışmışlardır. Bu çalışmada delâil’ün-nübüvve literatüründe ve nübüvveti konu edinen eserlerde Hz. Peygamber’in ahlâkının onun nübüvvetine delil oluş keyfiyetinin ortaya konulması amaçlanmaktadır.

Religion has a decisive function in every field and stage of human life. It establishes the relationship between the Creator and human beings and comprises teachings to attain us to happiness for this world (ad-dunya) and the hereafter (al-akhirah). The two essential bases of the Islamic religion are Theology and Prophethood. The relationship between the Creator, a transcendental being and the human beings who live in this physical world can be established via the Revelation and the Prophethood. The significance of the Prophethood in the Islamic thought is comprehended and the objections to this establishment have been discussed on an intellectual basis by the schools of Ilm al-Kalam, Philosophy and Islamic mysticism. Because the Islamic religion is universal, the Prophethood of the Prophet Muhammad concerns all the humanity. For this reason, the Prophethood of the Prophet Muhammad has been approached with different evidences and methods. Approaching the Prophethood from different point of views will provide to clear up the doubts of human beings whose nature, mental maturity and understanding are different from each other and also strengthen their beliefs. The Islamic philosophers who thought in this manner not only based the Prophethood of the Prophet Muhammad in miracles but also gave prominence to his virtue and they endeavoured to prove that such a perfect character could only be found in a Prophet. In this study, it is intended to describe the virtues of the Prophet Muhammad and to reveal how his character denote his Prophethood with regard to the literature of Dala’il on-Nobovvah (the evidences of the Prophethood) and the works dealing with the Prophethood.
Keywords: ahlâk The Prophethood; delail; evidences; Hz. Peygamber; Islam; İslam; morality; nübüvvet; Prophet Muhammad